2005
DOI: 10.1111/j.1365-2621.2005.tb09966.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Acrylamide in Fried Snack Products by Adding Amino Acids

Abstract: EE EE chips fried for 1.5 min at 185 °C. These results indicate that the addition of certain amino acids by soaking the uncooked products in appropriate solutions is an effective way of reducing acrylamide in processed foods. uncooked products in appropriate solutions is an effective way of reducing acrylamide in processed foods. uncooked products in appropriate solutions is an effective way of reducing acrylamide in processed foods. uncooked products in appropriate solutions is an effective way of reducing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 15 publications
5
50
0
1
Order By: Relevance
“…L-cysteine appeared to reduce the acrylamide content in the most effective way, with a reduction of about 92%, followed by L-lysine (39%) and glycine (24%). These results confirm previous investigations and above-mentioned hypotheses, although there were some differences in degree of reduction between different studies (Bråthen et al, 2005;Kim et al, 2005;Rydberg et al, 2003). Rydberg et al (2003) for instance found a more efficient acrylamide reduction of glycine compared to L-lysine in a potato model system.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modsupporting
confidence: 91%
See 1 more Smart Citation
“…L-cysteine appeared to reduce the acrylamide content in the most effective way, with a reduction of about 92%, followed by L-lysine (39%) and glycine (24%). These results confirm previous investigations and above-mentioned hypotheses, although there were some differences in degree of reduction between different studies (Bråthen et al, 2005;Kim et al, 2005;Rydberg et al, 2003). Rydberg et al (2003) for instance found a more efficient acrylamide reduction of glycine compared to L-lysine in a potato model system.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modsupporting
confidence: 91%
“…The addition of proteins or free amino acids other than asparagine such as glutamine, glycine, lysine or cysteine was also studied. These components would reduce acrylamide formation by promoting competitive reactions and/or by covalently binding the formed acrylamide through Michael type addition reactions (Bråthen, Kita, Knutsen, & Wicklund, 2005;Claeys, De Vleeschouwer, & Hendrickx, 2005;Cook & Taylor, 2005;Hanley et al, 2005;Kim, Hwang, & Lee, 2005;Low et al, 2006;Rydberg et al, 2003). Combined treatments with different amino acids (Hanley et al, 2005) or with an amino acid and organic acid (Low et al, 2006) could have an even greater potential to reduce acrylamide formation.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors diminished acrylamide formation in fried snacks products by adding amino acids, such as lysine, glycine and cysteine (Kim et al, 2005). The addition of glycine or glutamine during blanching of potato chips reduced the amount of acrylamide by almost 30% compared to control (Claeys et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the free amino acids glycine and L-lysine to the potato powder model system lowered the final acrylamide content, while keeping the pH at its original level. It was suggested that these components would reduce acrylamide formation by promoting competitive reactions and/or by covalently binding the formed acrylamide through Michael type addition reactions (Claeys, De Vleeschouwer, & Hendrickx, 2005;Kim, Hwang, & Lee, 2005;Low et al, 2006). Furthermore, organic acids, such as citric, acetic and Llactic acid reduced the final acrylamide content, but merely due to a reduced pH (Mestdagh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%